Memahami Penyembuhan Orang Buta dalam Yohanes 9:1-40 dengan Pendekatan Poskolonial - Vincent Kalvin Wenno (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
One of the important efforts in the postcolonial approach to biblical interpretation of the Bible is the emergence of other voices which so far have been marginalized due to the dominance of the structure or, and of a nation. The study is used in biblical texts, to see how domination takes place in text and interpretation, by seeing hegemonic power in a structure of society. The other voices to be raised in this article are the voices of persons with disabilities, especially in the text of John 9: 1-40. The text describes a long narrative about the miracle of healing a child who was born blind, who at the same time became a figure, who dared to voice his existence and identity, in the midst of fierce dialogue with Jews and Pharisees. In this narrative there is an attempt to read and interpret the text of John 9: 1-40 using the postcolonial approach. Abstrak Salah satu upaya penting dalam pendekatan postkolonial pada penafsiran Alkitab adalah memunculkan suara liyan yang selama ini termarjinalisasi akibat dominasi struktur atau, dan dari suatu bangsa. Studi tersebut digunakan ke dalam teks-teks Alkitab, untuk melihat bagaimana dominasi itu terjadi di dalam teks dan penafsiran, dengan cara melihat kuasa yang hegemonik dalam suatu struktur masyarakat tersebut. Suara liyan yang hendak dimunculkan di dalam artikel ini adalah suara dari para penyandang disabilitas terutama di dalam teks Yohanes 9:1-40. Teks tersebut mendeskripsikan narasi panjang tentang mukjizat penyembuhan anak yang terlahir buta, yang sekaligus menjadi tokoh, yang berani menyuarakan keberadaan dan identitasnya, di tengah dialog yang sengit dengan orang Yahudi dan Farisi. Dalam narasi inilah ada upaya untuk membaca dan menafsirkan teks Yohanes 9:1-40 dengan menggunakan pendekatan postkolonial.